Electrocardiography-based artificial intelligence predicts the upcoming future of heart failure with mildly reduced ejection fraction - Kim, Dae-Young; Lee, Sang-Won; Lee, Dong-Ho; Lee, Sang-Chul; Jang, Ji-Hun; Shin, Sung-Hee; Kim, Dae-Hyeok; Choi, Wonik; Baek, Yong-Soo (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHeart failure with mildly reduced ejection fraction (HFmrEF) has emerged as the predominant subtype of heart failure (HF). This study aimed to develop artificial intelligence (AI)-electrocardiography (ECG) to identify and predict the prognosis of patients with HFmrEF.MethodsWe collected 104,336 12-lead ECG datasets from April 2009 to December 2021 in a tertiary centre. The AI-ECG encompasses a novel model that combines an automatic labelling preprocessing method with a transformer architecture incorporating a triplet loss for HFmrEF analysis.ResultsThe receiver operating characteristic analyses revealed that the area under the curve of AI-ECG for identifying all types of HF was acceptable [0.873, 95% confidence interval (CI): 0.864–0.893], while that for identifying patients with HFmrEF was relatively lower (0.824, 95% CI: 0.794–0.863) than that for those with HF with reduced ejection fraction (EF) (0.875, 95% CI: 0.844–0.912) and those with normal EF (0.870, 95% CI: 0.842–0.894). The analysis of ECG features showed significant increases in QRS duration (p = 0.001), QT interval (p = 0.045), and corrected QT interval (p = 0.041) with increasing “Severity by Euclidean distance”. Following the predictability analysis with another group of 953 patients for improvements of follow-up EF in HFmrEF, the patients were grouped into three clusters based on the AI-Euclidean distance; Cluster 1 had the most severe cases and poorer outcomes than Clusters 2 (p < 0.001) and 3 (p < 0.001).ConclusionsAI-ECG presents an innovative approach for the prognostic stratification of cardiac contractility in patients with HFmrEF. In patients with HFmrEF, disease progression can be predicted using AI-ECG.